Occurrence and characterization of Bipolaris setariae associated with leaf blight of browntop millet (Brachiaria ramosa) in India. Issue 10 (31st July 2021) - Ramesh, Gutha Venkata; Palanna, Kaki Boraiah; Vinaykumar, Hargi Devappa; Arunkumar,; Koti, Prasanna S.; Mahesha, Hosapura Shekhararaju; Nagaraja, Thathigowdara Enkeswarappa; Tonapi, Vilas A.; Jeevan, B.
Abstract: A new leaf blight disease of browntop millet ( Brachiaria ramosa ) was noticed during rainy season ( Kharif ) 2018 at small millet experimental field, University of Agricultural Sciences, Gandhi Krishi Vignana Kendra (GKVK), Bengaluru, India. To assess the disease severity, an intensive roving survey was conducted during the 2019 cropping season. Based on the morphological characterization, the causal agent of leaf blight disease was identified as Bipolaris spp. Further sequencing and combined gene analysis of ITS (internal transcribed spacer of rDNA), GAPDH (glyceraldehyde 3‐phosphate dehydrogenase) and LSU (large subunit) of all the nine isolates confirmed the pathogen as B. setariae . Pathogenicity study showed that all the isolates were pathogenic and caused leaf blight symptoms on browntop millet. The B. setariae isolates showed marked variability with respect to disease incidence on browntop millet (cv. Dundu korale) under artificial inoculation conditions. However, the host range was limited only to browntop millet and found non‐pathogenic to other six small millets examined. To our knowledge, this is the first completely described study on characterization of B. setariae causing leaf blight disease of browntop millet in India.